Penyusunan Perangkat Pembelajaran Berbasis Multimedia Di SMA Negeri I STM Hilir - Guidio Leonarde Ginting; Imam Saputra; Putri Ramadhani (Forum Kerjasama Pendidikan Tinggi, 2022)
Improving the quality of education is a very important concrete element in efforts to improve the quality of human resources. To improve this quality, what needs to be considered is the problem of student achievement. Many factors cause students or students to fail academically, one of the factors is the less advanced and less modern education system. SMA Negeri I STM Hilir has a computer laboratory equipped with an internet connection. The laboratory is also equipped with a screen projector and projector so that it can be used to display subject matter using presentation slides to make it easier to simulate subject matter delivered by the teacher. However, the obstacle faced is the teacher's limitations in preparing material on presentation slides making the presentation slides that are displayed less attractive and making students less interested in paying attention to the material being taught. By looking at the problems faced by teachers at SMA N 1 STM Hilir, it is necessary to train teachers to make the most of multimedia-based learning tools so as to increase students' interest in learning. So that it has an impact on increasing students' understanding of the subject matter presented.